USING VISUAL AIDS TO ENHANCE VOCABULARY ACQUISITION IN FRENCH AS A FOREIGN LANGUAGE - Narzulloyeva Dilfuza Bahriddin qizi, (TADQIQOTLAR, 2025)
Abstract: This article examines the effectiveness of using visual aids in teaching French as a foreign language in increasing vocabulary. The study was conducted with A1  level  learners  and  analyzed  the  role  of  pictures, icons, charts, and other  visual materials in  memorizing  new  words,  using them  in  context, and  developing  active vocabulary. The article compares the results of the experimental and control groups, proving that visual aids can increase motivation and enhance efficiency in the learning process.